The Golgi 'casein kinase' Fam20C is a genuine 'phosvitin kinase' and phosphorylates polyserine stretches devoid of the canonical consensus. (20th November 2018) - Cozza, Giorgio; Moro, Enrico; Black, Miles; Marin, Oriano; Salvi, Mauro; Venerando, Andrea; Tagliabracci, Vincent S.; Pinna, Lorenzo A.
Abstract : Egg yolk phosvitins, generated through the fragmentation of vitellogenins (VTGs), are among the most heavily phosphorylated proteins ever described. Despite the early discovery in 1900 that chicken phosvitin is a phosphoprotein and its subsequent employment as an artificial substrate for a number of protein kinases, the identity of the enzyme(s) responsible for its phosphorylation remained a matter of conjecture until present. Here, we provide evidence that phosvitin phosphorylation is catalyzed by a family with sequence similarity 20, member C (Fam20C), an atypical protein kinase recently identified as the genuine casein kinase and responsible for the phosphorylation of many other secreted proteins at residues specified by the S‐x‐E/pS consensus. Such a conclusion is grounded on the following observations: (a) the levels of Fam20C and phosphorylated VTG rise in parallel upon treatment of zebrafish with oestrogens; (b) zebrafish phosvitin is readily phosphorylated upon coexpression in U2OS cells with Fam20C, but not with its catalytically inactive mutant; (c) a peptide reproducing a stretch of 12 serines, which are phosphorylated in chicken phosvitin despite lacking the C‐terminal priming motif S‐x‐E, is efficiently phosphorylated by both recombinant and native Fam20C. The last finding expands the repertoire of potential targets of Fam20C to include several proteins known to harbor (p‐Ser)n clusters not specified by any known kinase consensus. Abstract : Despite its early discovery in 1900, the kinase(s) responsible for the multiphosphorylation of egg yolk phosvitin remained a mystery until now. Here, we provide in vitro and in vivo evidence that the atypical kinase Fam20C, responsible for the generation of many secreted proteins, fulfills all criteria for being considered a genuine phosvitin kinase although many clusters of phosvitin phosphoserines lack their canonical priming consensus SSEE.